2021
DOI: 10.3390/app11041666
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Leukocyte-Platelet-Rich Fibrin (L–PRF) on Pain, Soft Tissue Healing, Growth Factors, and Cytokines after Third Molar Extraction: A Randomized, Split-Mouth, Double-Blinded Clinical Trial

Abstract: This study assessed the effects of leukocyte-platelet-rich fibrin (L–PRF) on soft tissue healing and the correlation with the local concentration of growth factors (GF) and cytokines in the dental socket of lower third molars. Forty lower-third molars (20 participants) were included in this randomized, double-blinded, split-mouth study. After extractions, randomized sides received alveolar filling with L–PRF on one side and a natural blood clot on the other side. The pain was assessed for up to seven days and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…In the metaanalysis by Xiang et al, (19), it was found that most studies revealed that application of PRF to extraction sockets significantly reduced pain on the postoperative third day and swelling on the postoperative first day. Soft tissue healing and cicatrization indices showed significant difference from baseline values only on the 7th day in most of the studies (20).…”
Section: Discussionmentioning
confidence: 85%
“…In the metaanalysis by Xiang et al, (19), it was found that most studies revealed that application of PRF to extraction sockets significantly reduced pain on the postoperative third day and swelling on the postoperative first day. Soft tissue healing and cicatrization indices showed significant difference from baseline values only on the 7th day in most of the studies (20).…”
Section: Discussionmentioning
confidence: 85%
“… 6 This can be the reason for the acceleration of wound healing with L-PRF, which has been seen in other intraoral surgeries, including tooth extraction. 7 , 9 This index is an observer-dependent index, and different indicators have been used in these studies. Perhaps these reasons can explain the differences in the results.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence on the use of L-PRF in oral applications suggests that it improves soft tissue wound healing, periodontal regeneration, and healing of extraction sockets. 7 - 9 In most of these procedures, L-PRF is placed below oral mucosal gingival flaps.…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, platelet-rich fibrin (PRF) has become increasingly popular in medicine and dentistry for its potential use in wound healing and tissue regeneration [ 4 , 5 , 6 , 7 , 8 ]. However, PRF’s development deviated from the typical research process as it was first used in humans before being studied in vitro and with animal models [ 9 ].…”
Section: Introductionmentioning
confidence: 99%